QUALIFICAÇÃO E CAPACITAÇÃO PROFISSIONAL COMO ESTRATÉGIA COMPETITIVA PARA O SETOR DE TURISMO / HOSPITALIDADE - Faria, Ana Maria Rocha (2003)
The objective of the present work went discuss it remains to qualification and the professional training in the tourist and hotel companies as one of the decisive strategic factors for the obtaining of the good result of its enterprises, as well as responsible largely for the success of the same ones. It was verified through studies, researches, managers' depositions and executives during the rising of data fact in elapsing of this investigation, that most of the professionals of the area just possesses empiric formation. Read with the hypothesis that the Brazilian hostelry registers accentuated need of professional formation for all the levels of the reception areas, management, restaurant, cooks and administration, that it should be based on a generality formation, more adapted to the demands of the section. The used methodology bases on the qualitative and quantitative research which limited to the period of 2002 and, whose universe embraced forty identified hotels of the city of Rio de Janeiro. As instrument of collection of data was used questionnaire which it was applied ten individuals between executives and operational managers, corresponding at 25% of the considered population. After comparative analysis between the result of the research and the revision of the literature the data aimed that has special meaning for this study in relation with all its challenges, the executives and managers of the nets consultation object when they indicate that the hotels are extremely faulty in the attempt of elevating the its employees' capacity to face the emergent demands of the market. Thus, the product of this work constitutes a valuable contribution concerning the understanding of the impact of the qualification and training of human resources for the competitiveness of the hotel companies, still stimulating plus, the discussion of several of its aspects and consequences.